A Comparative Study of Enhanced Infrared Image Processing for Foreign Object Detection in Lightweight Composite Honeycomb Structures; International Journal of Thermophysics; Vol. 39, iss. 12 - Zhang Hai; Sfarra S. Stefano; Genest M. Marc; Ibarra-Castanedo C. Clemente; Duan Yu. Yuxia; Fernandes H. C. Henrique Coelho; Avdelidis N. P.; Maldague X. Xavier (2018, 2018)
Title screen